GENETIC DIVERSITY OF FABA BEAN (VICIA FABA L.) POPULATIONS ESTIMATED BY ISOZYMIC AND MOLECULAR MARKERS: RELATIONSHIP BETWEEN THE TWO METHODS - Ouji, Ali; El-Bok, Safia; Rouaissi, Mustapha; Syed, Naeem H.; Suso, Maria Jose; Flavell, Andrew J.; El Gazzah, Mohamed; Younes, Mongi Ben; Kharrat, Mohamed (European Scientific Journal, ESJ, 2015)
In our previous studies, the genetic diversity among nine Tunisian faba bean (Vicia faba) populations was analysed using isozymes and sequence-specific amplification polymorphism (SSAP) markers. The objectives of this study were to compare the application and utility of isozymes and sequence-specific amplification polymorphism (SSAP) techniques for analysis of genetic diversity among nine Tunisian faba bean (Vicia faba) populations. A high genetic diversity within populations was detected by both isozymes (SOD, 6-PGD, ME, EST, SKDH, FDH and GDH) and (SSAP) markers (PDR1, Tps19 and Tvf4). For all populations, the genetic diversity revealed by SSAP was more pronounced than that detected with isozyme, based on polymorphic profiles. The analyses of correspondance between the tow methodes based in Mantel test revealed a low correlation ( r=0.177). The low correspondance indicated the absence of correlation and therfore the complimentarity